Makna simbolik bahasa ritual pertanian masyarakat Bali - Ni Wayan Sartini (Pusat Kajian Bali Universitas Udayana, 2017)
The purpose of this study is to conserve the agricultural culture and to review the symbolic meaning and local wisdom in certain agricultural rituals. This research is conducted in Subak Kedua Pasedahan Yeh Lauh, Peguyangan Kangin Village, West Denpasar, Bali. Data is collected using the methods of interview and literature review. From the data collected, there are twenty four ritual steps found that should be performed by the farmers in Bali. Those indicate farmers’ religious nature and appreciation of their cultural tradition. Each ritual from sowing to harvesting contains symbolic meanings and cultural values embraced as the guidance in farming life. From the analyses concerning its ritual and tools used, it is concluded that the symbolic meaning of ritual discourse performed by the farmers are: (1) expressing gratitude to God for all abundant harvest grace; (2) asking permission for farming to the motherland as the manifestation of God in term of the ruler of the land; (3) asking for safety for having a successful agriculture to God (Goddess Sri); (4) offerings to the rice field rulers to be kept away from pests that damage plants; (5) keeping the environmental balance –in the philosophy of Hindu society in Bali, it is one of Tri Hita Karana’s best practices.